Quality of Life (QoL) in patients with Traumatic Brain Injury (TBI): A Literature Review - Sukraeny, Nury; Songwathana, Praneed; Sae-Sia, Wipa (Nurse Media Journal of Nursing, 2013)
Purpose: To describe the definition of quality of life (QoL) and identify the most appropriate tool for QoL assessment used in patients with TBI.Method: Searching was conducted from PubMed, CINAHL, EBSCO, and ProQuest during 2000-2011. A total of 33 studies were analyzed for this review consisting of 9 review studies, 2 intervention studies, and 22 descriptive studies.Result: Two important definitions of QoL were used in studies related to TBI namely achievement and subjective well-being. Although varieties of generic measurements have been used to measure QoL in TBI patients, there was a lack of TBI-specific Health-related Quality of Life (HRQoL) instrument. Despite the different approach and time measured either short or long outcomes, appropriate domains of QoL tool seem essential particularly among those with moderate and severe TBI.Conclusion: QoL is a wide concept which can be defined in several dimensions. The QOLIBRI as a new disease-specific QoL measurement in TBI seems a feasible and valid approach for the assessment of QoL in TBI. However, the application across cultural remains a challenge and needs a validation.